The effects of prone positioning on the respiratory mechanics of patients with Covid-19 at the intensive care center: a systematic review (Research, Society and Development, 2021)
Corona Virus Disease-19 (Covid-19) is a disease caused by SARS-CoV-2, which has reached the status of a pandemic and has dramatically increased the need for admissions to Intensive Care Units (ICU's). In this context, the use of techniques for the support and care of the sick highlighted the prone position, a conduct on which several studies elucidate the physiological benefits for the respiratory system. To investigate the effects of applying prone positioning in the intensive care setting in patients with Covid-19, exploring the benefits and pointing out the possible counterpoints of this therapy. Bibliographic survey in the VHL (MEDLINE and LILACS) and PUBMED databases. The study included 13 articles in Portuguese and English, published in the last 5 years. Development: Most studies analyzed confirm the feasibility and safety of applying prone positioning in patients with Covid-19, where there is considerable improvement in peripheral oxygenation and ventilation-perfusion ratio, although some studies have not found significant results. It is concluded that the technique is safe and effective and it is noted that the pronation period and patient adherence to therapy, when awake, can be a determining factor for treatment success.